POTRET ETNIS OSING DARI SEGI SOSIAL, BUDAYA, DAN EKONOMI DI DESA KEMIREN, GLAGAH, KABUPATEN BANYUWANGI - I Kadek Yudiana; Mahfud; Eka Prasetya Suryadani (Yayasan Nusantara Hasana Berdikari, 2023)
Kemiren Village has a variety of customs and culture that have special characteristics and are still maintained today. This is what made Kemiren Village a traditional village. The purpose of this study was to find out the social, cultural and economic life of the Osing people in Kemiren Village, Glagah, Banyuwangi. The research method used is descriptive qualitative. Data collection techniques using interviews, observation, and document study. Data analysis techniques use the theory of Miles and Huberman (2014), namely, data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that by making it a traditional village, Kemiren Village has positive and negative impacts in terms of social, culture and economy. Osing's Ethnic strategy in dealing with change includes the use of customary law, socialization carried out by village officials to increase community participation in developing the village, and maintaining the local wisdom of the Osing community in Kemiren Village, so that it remains in accordance with values ​​and norms.